Analisis Perbedaan Pengaruh Probabilitas (ROA) Terhadap Harga Saham Sebelum Dan Saat Pandemi Covid-19: (studi kasus pada perusahaan Telekomunikasi) - Ronald N Girsang (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The Covid-19 pandemic phenomenon also has an impact on the economic and business sectors. The IHSG trend has decreased since the Covid-19 pandemic case was announced. Rises and falls in share prices can be caused by financial performance factors. This research examines whether there is a difference in the influence of ROA on share prices both before and during the pandemic. The objects in this research are all telecommunications companies, with a purposive sampling method, the sample obtained in this research was 13 companies, namely telecommunications companies that published share prices before the Covid-19 pandemic as many as 13 and during the Covid-19 pandemic as many as 13. Using this method Simple linear regression shows that ROA has an effect on stock prices before the pandemic, and ROA has an effect on stock prices during the pandemic. ROA for telecommunications companies was 12.7% before the pandemic, increasing to 24.2% during the pandemic. This means that a pandemic event can increase the relationship between ROA and share prices.